Comprehensive Description of Pathogens and Antibiotic Treatment Guidance in Children With Community-Acquired Pneumonia Using Combined Mass Spectrometry Methods - Sun, Liying; Zhang, Chi; An, Shuhua; Chen, Xiangpeng; Li, Yamei; Xiu, Leshan; Xu, Baoping; Xie, Zhengde; Peng, Junping (Frontiers in Cellular and Infection Microbiology, 2021)
Abstract The objective of this study was to evaluate the value of molecular methods in the management of community-acquired pneumonia (CAP) in children. Previously developed mass spectrometry (MS)-based methods combined with quantitative real-time PCR (combined-MS methods) were used to describe the aetiology and evaluate antibiotic therapy in the enrolled children. Sputum collected from 302 children hospitalised with CAP were analysed using the combined-MS methods, which can detect 19 viruses and 12 bacteria related to CAP. Based on the results, appropriate antibiotics were determined using national guidelines and compared with the initial empirical therapies. Respiratory pathogens were identified in 84.4% of the patients (255/302). Co-infection was the predominant infection pattern (51.7%, 156/302) and was primarily a bacterial-viral mixed infection (36.8%, 111/302). Compared with that using culture-based methods, the identification rate for bacteria using the combined-MS methods (61.8%, 126/204) increased by 28.5% (p <0.001). Based on the results of the combined-MS methods, the initial antibiotic treatment of 235 patients was not optimal, which mostly required switching to β-lactam/β-lactamase inhibitor combinations or reducing unnecessary macrolide treatments. Moreover, using the combined-MS methods to guide antibiotic therapy showed potential to decrease the length of stay in children with severe CAP. For children with CAP, quantitative molecular testing on sputum can serve as an important complement to traditional culture methods. Early aetiology elucidated using molecular testing can help guide the antibiotic therapy.